Origin and spatial population structure of Malagasy native chickens based on mitochondrial DNA - Takahiro Yonezawa; Hideyuki Mannen; Kaho Honma; Megumi Matsunaga; Felix Rakotondraparany; Fanomezana Mihaja Ratsoavina; Jiaqi Wu; Masahide Nishibori; Yoshio Yamamoto (Scientific Reports, 2024)
Abstract Since Malagasy human culture became established in a multi-layered way by genetic admixture of Austronesian (Indonesia), Bantu (East Africa) and West Asian populations, the Malagasy native livestock should also have originated from these regions. While recent genetic studies revealed that Malagasy native dogs and goats were propagated from Africa, the origin of Malagasy native chickens is still controversial. Here, we conducted a phylogeographic analysis of the native chickens, focusing on the historical relationships among the Indian Ocean rim countries and based on mitochondrial D-loop sequences. Although previous work suggested that the rare Haplogroup D occurs with high frequencies in Island Southeast Asia–Pacific, East Africa and Madagascar, the major mitochondrial lineage in Malagasy populations is actually not Haplogroup D but the Sub-haplogroup C2, which is also observed in East Africa, North Africa, India and West Asia. We demonstrate that the Malagasy native chickens were propagated directly from West Asia (including India and North Africa), and not via East Africa. Furthermore, they display clear genetic differentiation within Madagascar, separated into the Highland and Lowland regions as seen in the human genomic landscape on this island. Our findings provide new insights for better understanding the intercommunion of material/non-material cultures within and around Madagascar.